PENGUATAN PENDIDIKAN ASWAJA AN-NAHDLIYAH UNTUK MEMPERKOKOH SIKAP TOLERANSI - Amir, Amir; Baharun, Hasan; Aini, Lina Nur (JURNAL ISLAM NUSANTARA, 2020)
This research focuses on an effort to analyze the strengthening of Aswaja An-Nahdliyah education which is carried out to strengthen the tolerance attitude of the madrasa which has started to fade. This research used a qualitative approach to the type of case study, with the research site at Madrasah Tsanawiyah (MTs) Al-Hidayah, Kangean, Sumenep, Madura. The data collection technique is done through observation, interview and documentation. While the data analysis was carried out in stages, starting from data display, data reduction to drawing conclusions. The results showed that Aswaja An-Nahdliyah Education in strengthening tolerance attitudes in MTs. Al-Hidayah is carried out through the internalization of Aswaja An-Nahdliyah education in the madrasah curriculum structure, strengthening the local content of Aswaja An-Nahdliyah, building a culture of tolerance and the formation of the NU student organization.